A Novel Micronutrient Supplement to Mitigate the Transgenerational Effects of Paternal Obesity on Body Composition of Male Offspring (P11-138-19) - Billah, Md Mustahsan (Curr Dev Nutr, 2019)
OBJECTIVES: Emerging evidence suggests that paternal obesity plays a significant role on offspring health. Our previous work in rodents showed that high fat diet (HFD) induced paternal obesity reduced offspring glucose tolerance. It has also been reported that paternal obesity can initiate metabolic disturbance in subsequent generations. Therefore, we designed a novel micronutrient supplement to ameliorate the transgenerational effects of paternal obesity. METHODS: Founder (F0) male Sprague Dawley rats (3 weeks, 12 per group) were weaned on control (CD) or HFD or diets containing micronutrient supplement (CS; HS), after which they were mated with CD fed females at 19 weeks of age. Twelve F1 offspring from each litter across the four diet groups were weaned on day 21 onto CD, generating four F1 groups. After 14 weeks on CD, they were mated with CD fed females. Male F2 siblings were fed CD or HFD from day 21. After 6 weeks on diet, they underwent EchoMRI (See attached study design). RESULTS: HFD increased adiposity (CD: 12.3%, HFD: 18.6%) in F0 which was normalized by supplementation (HS: 11.7%). Though no paternal effect on adiposity was found in F1 males across the four groups, supplementing F0 had significant impact on F2 body composition (fat mass, fat and lean percentage) without influencing body weight and lean mass after 6 weeks on diet. In F2, post weaning HFD significantly increased fat mass in rats from CD and HFD fed founders (CH vs CC P = 0.0001; HH vs HC P = 0.009) but this effect was significantly reduced by F0 supplementation irrespective of F0 diets (CSH vs CH P = 0.017; and HSH vs HH P = 0.04) [3-way ANOVA][See attached table]. Moreover, lean percentage was decreased by post weaning HFD in rats from both non-supplemented F0 diet groups but interestingly this effect was significantly reduced only in rats sired by supplemented CD fed F0 (CSH > CH; P = 0.04). CONCLUSIONS: Supplementing CD fed grandfathers ameliorated the deleterious effect of HFD, decreasing fat deposition and increasing lean percentage whereas supplementing HFD fed F0 reduced only fat deposition without affecting lean mass of male grand offspring. Therefore, our designed supplement could eventually reduce the transgenerational effect of paternal obesity. FUNDING SOURCES: Supported by Australian NHMRC grant to MJM and CAM; MMB is supported by Scientia PhD Scholarship, UNSW. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: